Strategi dan Solusi Layanan Bimbingan Konseling Di Masa Pandemi Covid-19 - Yuni Chotimawati (JCOSE Jurnal Bimbingan dan Konseling, 2021)
Guidance and counseling service is an integral part of the educational process in the education unit. During the Covid-19 pandemic, strategies and solutions are needed so it can be carried out online. Whatsapp is a social media that has been widely known and used by many people in Indonesia. The features found on Whatsapp support the implementation of online guidance and counseling service including its supporting activities such as classical formats, group formats, and individual formats. Classical format and group format services can be carried out through one of Whatsapp features known as Whatsapp Messenger Group, while individual format services can be conducted through Whatsapp Chat. However, there are some obstacles faced in using Whatsapp as a medium for online guidance and counseling services. Some of the obstacles that often arise are unstable signal, insufficient memory on cellphone due to many files received, lack of interaction between teachers and students, difficulty to check the seriousness of students, lack of student motivation, lack of supporting devices, and difficulty to understand the material given. However, despite all the obstacles that may occur, as a user friendly platform and very popular in Indonesia and even in the world, Whatsapp can still be used as a strategic media and solution for guidance and counseling service during the Covid-19 Pandemic.